Greenly Reduced CoFe‐PBA/Nickel Foam: A Robust Dual Electrocatalyst for Solar‐Driven Alkaline Water Electrolysis with a Low Cell Voltage. Issue 33 (1st September 2022) - Vishnu, Bakthavachalam; Mathi, Selvam; Sriram, Sundarraj; Jayabharathi, Jayaraman
Abstract: Development of eco‐friendly efficient dual electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) gaining increased attention for renewable energy production. Here, the greenly synthesized rCoFe‐PBA was established as durable and effective bifunctional electrocatalyst for HER and OER process. The rCoFe‐PBA coated Nickel foam electrode exhibit overpotential of 311 mV (OER) and 100 mV (HER) @ 10 mA cm −2 significantly lower than commercial IrO2 (381 mV) and near to Pt/C (36 mV). The rCoFe‐PBA show smaller Tafel slope (OER: 57 mV dec −1 ) than IrO2 (78 mV dec −1 ) and exhibit Tafel slope of 131 mV dec −1 (HER) which is near to Pt (90 mV dec −1 ). Turnover frequency (TOF) was estimated as 0.22 s −1 (OER) and 0.26 s −1 (HER) was found to be 5 and 10 times higher than IrO2 catalyst (0.040 s −1 ) and Pt/C catalyst (0.025 s −1 ), respectively. For solar water electrolysis, rCoFe‐PBA/NF shows overpotential of 411 mV and durability over 180 h in 1.0 m KOH (4.1 % potential loss). The combination of non‐precious electrolyzer, rCoFe‐PBA with commercial solar cell produced H2 gas in alkaline water under sunlight. This methodology proves that the greenly synthesized rCoFe‐PBA electrolyzer can outperform the precious electrocatalysts, implying that the cost‐effective large scale H2 production without artificial current is possible with commercial solar cells. Abstract : Water electrolysis offers a potential route for producing sustainable H2 fuel. The overpotential of greenly synthesized rCoFe‐PBA become 311 mV (OER) and 100 mV (HER) lower than that of IrO2 (421 mV) and Pt (36 mV), respectively. In overall water splitting, rCoFe‐PBA has a long‐term stability of 180 hours with 6.4 % voltage loss in 1.0 m KOH. At 1.64 V, the solar water electrolysis exhibits continuous development of oxygen and hydrogen gas at the anode and cathode, respectively.